Two monitored cases of sudden death outside hospital. Issue 6 (June 1978) - Pool, J; Kunst, K; van Wermeskerken, J L
Abstract : Two patients known to have coronary artery disease died suddenly outdoors while active. Neither had symptoms or signs of acute myocardial infarction. They were being monitored by continuous tape recording of the electrocardiogram at the time of death. In one patient the cause of death was cardiac arrest, preceded by bigeminy and multiform ventricular ectopic beats, in the other ventricular fibrillation preceded by atrial fibrillation, multiform ventricular ectopic beats, and ST depression. These observations are added to the limited reported cases in which the mechanism leading to sudden death outside the hospital is recorded.